PENINGKATAN KINERJA YANG DIPENGARUHI OLEH KOMPETENSI, MOTIVASI DAN DISIPLIN KERJA : Studi Kinerja Pegawai Kecamatan Pademawu Kabupaten Pamekasan - Holilah Holilah; Chamariyah Chamariyah; Indra Prasetyo (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2021)
Holilah, 2021. Performance Improvement Influenced by Competence, Motivation and Work Discipline (Performance Study of Employees of Pademawu District, Pamekasan Regency). Postgraduate Program at Wijaya Putra University, Surabaya. This research includes explanatory research. The research method used is the survey method, which is the method used to obtain information through requests for information to respondents by using a questionnaire as the main data collection tool. The sampling technique used is total sampling, meaning that the sampling technique is the same as the total population, there are 64 respondents in this study. The aims of this study were to: (1) examine and analyze the simultaneous/simultaneous effect of competence, motivation and work discipline on employee performance in Pademawu Subdistrict, Pamekasan Regency, (2) to examine and analyze the relationship between the influence of competence on employee performance in Subdistrict Pademawu, Pamekasan Regency, (3) to test and analyze the relationship of the influence of motivation on the performance of employees in Pademawu District, Pamekasan Regency, (4) to examine and analyze the relationship between the influence of work discipline on the performance of employees in Pademawu District, Pamekasan Regency. The results of this study indicate that: (1) Competence, motivation and work discipline simultaneously affect the performance of employees in Pademawu District, Pamekasan Regency with a calculated F test value of 4,556 with a significant level of 0.04. (2) Competence has a partial effect on employee performance in Pademawu District, Pamekasan Regency with a t-test value of 2.638 with a significant level of 0.03. (3) Motivation has a partial effect on employee performance in Pademawu District, Pamekasan Regency with a t-test value of 1.822 with a significant level of 0.04. (4) Work discipline has a partial effect on employee performance in Pademawu District, Pamekasan Regency with a t-test value of 2.852 with a significant level of 0.02.